Affective commitment of university students: Definition and proposals for improvement - Olmedo-Cifuentes, Isabel; Martínez-León, Inocencia M.; Ramón-Llorens, M. Camino; Sánchez-Casado, Noelia (Revista Complutense de Educación, 2025)
Introduction: This paper studies how certain sociodemographic aspects along with variables such as university experience, academic motivation, and academic satisfaction influence university students’ affective commitment. Method: Empirical research based on 191 surveys of students from a Spanish public university is conducted to test the proposed hypotheses. Variables were analyzed with a hierarchical linear regression. Results: Student affective commitment is mainly determined by academic satisfaction and university experience, with academic motivation not having a significant influence. It is also observed that the youngest students have higher affective commitment, as well as those who study degrees closer to the social sciences. The differences between students who have considered dropping out of their studies and those who have not are analyzed. The affective commitment of the former is determined by the university experience, academic satisfaction, and the course in which they are; while those who have not considered quitting their studies present similar results to the global sample. Discussion: Some recommendations are suggested to university institutions to improve affective commitment, where the stimulus of a pleasant university experience is critical.